2021
DOI: 10.1080/21655979.2021.1995104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlations and prognostic value of Nudix hydroxylase 10 in patients with gastric cancer

Abstract: Gastric cancer (GC) is one of the most common and lethal cancers worldwide. The Nudix hydroxylase (NUDT) genes have been reported to play notable roles in tumor progression. However, the role of NUDT10 in GC has not been reported. In this study, we investigated the expression of NUDT10 in GC and its association with clinicopathological characteristics. Quantitative real-time polymerase chain reaction and analyses of The Cancer Genome Atlas and Human Protein Atlas databases were performed to determine NUDT10 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Research by Kamdar et al has shown that reduced level of NUDT10 may improve promoter methylation in prostate cancer by showing tumoral suppressive characteristics (Kamdar et al, 2019). Similar to our study, a recent study has been concluded that the expressions of NUDT10 mRNA and protein in gastric cancer samples were remarkably reduced than those in controls (Chen D. et al, 2021).…”
Section: Figuresupporting
confidence: 92%
“…Research by Kamdar et al has shown that reduced level of NUDT10 may improve promoter methylation in prostate cancer by showing tumoral suppressive characteristics (Kamdar et al, 2019). Similar to our study, a recent study has been concluded that the expressions of NUDT10 mRNA and protein in gastric cancer samples were remarkably reduced than those in controls (Chen D. et al, 2021).…”
Section: Figuresupporting
confidence: 92%
“…m7G regulators are prognostic markers of a variety of cancers. METTL1 and WDR4 are highly expressed in a variety of tumors, such as liver cancer ( Chen D et al, 2021 ), intrahepatic cholangiocarcinoma ( Dai S et al, 2021 ), and lung cancer ( Ma et al, 2021 ), which is related to poor prognosis of patients. High expression of NSUN2 is associated with poor prognosis of gastric cancer ( Hu J et al, 2021 ) and esophageal squamous cell carcinoma ( Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…NUDT10 is a member of the nucleoside diphosphate-linked moiety X (NUDIX) hydroxylases. Research indicates that for patients with GC, NUDT10 expression is related to the disease stage, level of local invasion, and survival outcome ( 56 ). POLR2I encodes a subunit of RNA polymerase II, the polymerase responsible for synthesizing mRNA in eukaryotes and has potential as a novel biomarker for colorectal cancer metastasis ( 57 ).…”
Section: Discussionmentioning
confidence: 99%